The impact of collateral therapeutics on stroke hemodynamics in normotensive and hypertensive rats: a step toward translation - Cipolla, Marilyn J.; Hunt, Ryan D.; Liebeskind, David S.; Tremble, Sarah M. (Frontiers in Neurology, 2024)
Introduction Stroke interventions that increase collateral flow have the potential to salvage penumbral tissue and increase the number of patients eligible for reperfusion therapy. We compared the efficacy of two different collateral therapeutics during transient middle cerebral artery occlusion (tMCAO) in normotensive and hypertensive rats. Methods The change in collateral and core perfusion was measured using dual laser Doppler in response to either a pressor agent (phenylephrine, 10 mg/kg iv or vehicle) or a collateral vasodilator (TM5441, 5 mg/kg iv or vehicle) given 30 min into tMCAO in male Wistar and spontaneously hypertensive rats (SHRs). Results Pressor therapy increased collateral flow in the Wistar rats but was ineffective in the SHRs. The increase in collateral flow in the Wistar rats was associated with impaired cerebral blood flow autoregulation (CBFAR) that was intact in the SHRs. TM5441 caused a decrease in collateral perfusion in the Wistar rats and a modest increase in the SHRs. The pressor therapy reduced early infarction in both groups but increased edema in the SHRs, whereas TM5441 did not have any beneficial effects in either group. Conclusions Thus, the pressor therapy was superior to a collateral vasodilator in increasing collateral flow and improving outcomes in the Wistar rats, likely due to pial collaterals that were pressure passive; the lack of CBF response in the SHRs to pressor therapy was likely due to intact CBFAR that limited perfusion. While TM5441 modestly increased CBF in the SHRs but not in the Wistar rats, it did not have a beneficial effect on stroke outcomes. These results suggest that collateral therapies may need to be selected for certain comorbidities.